If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 130 = 2x + 6(2x + -4) Reorder the terms: 130 = 2x + 6(-4 + 2x) 130 = 2x + (-4 * 6 + 2x * 6) 130 = 2x + (-24 + 12x) Reorder the terms: 130 = -24 + 2x + 12x Combine like terms: 2x + 12x = 14x 130 = -24 + 14x Solving 130 = -24 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 130 + -14x = -24 + 14x + -14x Combine like terms: 14x + -14x = 0 130 + -14x = -24 + 0 130 + -14x = -24 Add '-130' to each side of the equation. 130 + -130 + -14x = -24 + -130 Combine like terms: 130 + -130 = 0 0 + -14x = -24 + -130 -14x = -24 + -130 Combine like terms: -24 + -130 = -154 -14x = -154 Divide each side by '-14'. x = 11 Simplifying x = 11
| (78x-67y)-(49x+33y)= | | 3m+6m+7m-9= | | P-2k=7 | | 3/5x-1/5x=-3 | | n-5/7=4 | | 7(4)+4y=56 | | 7x+4(0)=56 | | 2y-3x=50 | | 16x^2-72x=15 | | 7(0)+4y=56 | | 1-(8)/(x+1)^3=0 | | (4x+2)/5*9=-18 | | 3a+20-a+10=180 | | 3[6s+12]-[10s-6]=0 | | 0.5n=0.35 | | 12x+4-8=2x-22 | | ((3^3-10)+(-7))/((-5)^2+(-4x-5)) | | 52=2x+4(x+4) | | 5+4e^2x=20 | | (65x+63y)-(26x-4y)= | | (60x+63y)-(-43x+13y)= | | x^3-3x^2+3x+6=0 | | 9(2x-6)=3(6x+9) | | 9(y-2)+5(6y-18)-13y=-4 | | 6-5x+9+3x+3x-2=8+3(4) | | 5y-10=4y-1 | | 8+18z-3=9z+35-6z | | 0=(3x+2)(4x-1) | | [3x-4(x+1)]=2 | | 5p+9p=70 | | -4m-7+13m-12+2m-5= | | p^2+11+10=0 |